Peran Pemerintah Kelurahan dalam Pemberdayaan Masyarakat di Kelurahan Tamaona Kabupaten Gowa - Muh Zulkarnain (Departemen Ilmu Pemerintahan Fisip Unhas, 2018)
This study aims to determine The Role of Village Government in Community Empowerment in Tamaona Village in Gowa regency As well as the factors that influence it and the factors that influence it. To Archive the target. This Research Used qualitative research methods by parsing data descriptively. Technique of data collecting done by observation and interview. As well as documents and archives using qualitative descriptive analysis techniques.The results showed: First, the role of government as a coach focuses on human development by providing counseling and socialization of the program, business development by providing capital assistance, seed assistance, agricultural fertilizer, community development built in the spirit of mutual cooperation and instilling religious values in the community, and institutional development by establishing harmonious relationships, Provide direction and support to community institutions in Tamaona Urban Village. Both, factors affecting community empowerment in Kelurahan Tamaona Kabupaten Gowa include supporting and inhibiting factors. Supporting factors are community participation, community awareness and education level of the community. The factors that become obstacles are budget constraints, people's mindset and binding rules